2011
DOI: 10.1039/c1cp21194c
|View full text |Cite
|
Sign up to set email alerts
|

Role of micro-structure and interfacial properties in the higher photocatalytic activity of TiO2-supported nanogold for methanol-assisted visible-light-induced splitting of water

Abstract: This paper deals with the textural, microstructural and interfacial properties of Au/TiO(2) nanocomposites, in relation to their photocatalytic activity for splitting of water. TiO(2) samples of two different morphologies were employed for dispersing different cocatalysts, such as: Au, Pt, Ag or Cu, for the sake of comparison. The samples were characterized using powder XRD, XPS, UV-visible, thermoluminescence, SEM, HRTEM and SAED techniques. Compared to other metal/TiO(2) photocatalysts, Au/TiO(2) with an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…A small fraction of the CH 2 O product desorbs during irradiation, as evidenced by a TOF signal of CH 2 O (Figure 9), which corresponds to desorption of ∼0.01 ML during the first 30 min of irradiation. Most of the disappearance of CH 2 O appears to be from conversion to formate, as revealed in the TPD spectra shown in Figure 10, which were collected at m/z = 28(C 2 40 and the cracking pattern of HCOOH collected with our mass spectrometer, we concluded that the 486 K peak 3 OH was dosed first. The m/z ratios correspond to fragments of various possible isotopic variants of methanol, formaldehyde, and methyl formate.…”
Section: Results and Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…A small fraction of the CH 2 O product desorbs during irradiation, as evidenced by a TOF signal of CH 2 O (Figure 9), which corresponds to desorption of ∼0.01 ML during the first 30 min of irradiation. Most of the disappearance of CH 2 O appears to be from conversion to formate, as revealed in the TPD spectra shown in Figure 10, which were collected at m/z = 28(C 2 40 and the cracking pattern of HCOOH collected with our mass spectrometer, we concluded that the 486 K peak 3 OH was dosed first. The m/z ratios correspond to fragments of various possible isotopic variants of methanol, formaldehyde, and methyl formate.…”
Section: Results and Analysismentioning
confidence: 95%
“…A study of CH 2 ) for 0.5 ML of CH 3 OH adsorbed initially on TiO 2 (110). The decomposition of CH 3 OH to CH 2 O and HCOOCH 3 results in surplus H atoms, which transfer to BBO sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Gold nanoparticles supported on titania exhibit photocatalytic activity for water splitting under uv, visible, and near-infrared light. [8][9][10] When they have landed on a surface, different atomic configurations of gold cluster have been found depending on the nature of the supporting substrate, for instance, atomic chains on NiAl(110), 11 two-dimensional (2D) plates on alumina/NiAl(110), 12 and three-dimensional (3D) clusters on iron oxide and titania. 13,14 In general small Au nanoparticles maintain high stability even in water solutions, making them suitable for catalytic applications.…”
Section: Introductionmentioning
confidence: 99%